(untitled) - Shapiro, Alan C. (Boston, 1994)
This work emphasizes concepts and practices, and features real-world examples that provide actual applications of financial concepts and theories, showing how the issues, tools and techniques of financial analysis and reasoning are being applied.
Keywords: International business enterprises,Decision making,Hoạt động kinh doanh quốc tế,Ra quyết định; Finance,Tài chính